Examining primary school students performance in solving problems requiring realistic considerations - KÄ±lÄ±Ã§, Ã‡iğdem; Åžahinkaya, Nihan (Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
Problem-solving is a very important topic in mathematics education. There are various types of problems in the literature. One of them is non-standard word problems. The main purpose of this study is to examine the problems faced by primary school fourth-grade students in solving non-standard word problems. For this purpose, a problem-solving questionnaire consisting of a total of four questions was applied to 250 primary school fourth-grade students and the students' answers were examined in detail. It was determined that the percentage of correct answers given by the students to the problems varied depending on the nature of the problems. In general, it was concluded that although the students chose the correct mathematical operations for the solutions, they did not use real-life knowledge in solving the problems and therefore their results were not realistic and correct. Therefore, it was observed that non-standard problem-solving activities that require the use of real-life knowledge should be included more in classrooms.